EZH2 inhibition suppresses bladder cancer cell growth and metastasis via the JAK2/STAT3 signaling pathway - Chen, Zhiyuan (Oncol Lett, 2019)
The aim of the current study was to investigate the role of enhancer of zeste 2 polycomb repressive complex 2 subunit (EZH2) in the progression of bladder cancer. Human bladder cancer tissue samples were analyzed by immunohistochemistry, and the association between the clinicopathological parameters and EZH2 expression was analyzed. The proliferation, apoptosis and migration ability of the human bladder cancer cell lines E-J and 5637 with or without the EZH2 inhibitor UNC1999 was investigated. The effect of UNC1999 was further explored in a xenograft model of nude mice. The in vivo and in vitro expression levels of EZH2, janus kinase 2, signal transducer and activator of transcription 3 and their phosphorylated forms were examined by western blotting. The expression levels of EZH2, JAK2 and STAT3 were increased in bladder cancer tissue compared with normal adjacent tissue. Furthermore, the expression of EZH2 was increased in tumors with a higher TNM Classification of Malignant Tumors stage and histological grade compared with tumors with a lower stage and grade. The human bladder cancer cell lines E-J and 5637 treated with UNC1999 demonstrated reduced cell proliferation, apoptosis and migration compared with cells treated without UNC1999. Additionally, EZH2 may promote the proliferation and migration of bladder cancer via the JAK2/STAT3 pathway. EZH2 may serve an important role in the proliferation and migration of human bladder cancer cells, and may aid in the development of novel treatment strategies for bladder cancer.